2018
DOI: 10.2174/1568026618666180601080824
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Perspective on the Modulation of Protein-Protein Interactions with Small Molecules

Abstract: Protein-Protein Interactions (PPIs) are the key components in many cellular processes including signaling pathways, enzymatic reactions and epigenetic regulation. Abnormal interactions of some proteins may be pathogenic and cause various disorders including cancer and neurodegenerative diseases. Although inhibiting PPIs with small molecules is a challenging task, it gained an increasing interest because of its strong potential for drug discovery and design. The knowledge of the interface as well as the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fragmentation of protein molecules. Fragments of protein molecules were originally hypothesized to be non-functional peptide segments; however, recent studies have revealed that they have important functions (109,110). These can be secreted as hormone molecules into the extracellular space, transported to target organs and serve similar or opposite roles with protein precursors (109).…”
Section: Study On New Polypeptides In Obesitymentioning
confidence: 99%
“…Fragmentation of protein molecules. Fragments of protein molecules were originally hypothesized to be non-functional peptide segments; however, recent studies have revealed that they have important functions (109,110). These can be secreted as hormone molecules into the extracellular space, transported to target organs and serve similar or opposite roles with protein precursors (109).…”
Section: Study On New Polypeptides In Obesitymentioning
confidence: 99%
“…In this area, some covalent PPI inhibitors seem to have also a promising future [14,15]. HTS, virtual screening, fragment-based approaches and the search for peptidomimetics are among the most explored strategies in route towards PPI modulators [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%